Understanding organizational injustice: are injustice and justice polar opposites? - Palmer, Christa E., author; Byrne, Zinta S., advisor; Gibbons, Alyssa M., committee member; Henry, Kimberly L., committee member; Hogler, Raymond L., committee member (Colorado State University. Libraries, 2010)
The goal of this study is to clarify our understanding of organizational injustice. It appears that the extant research has assumed that organizational justice is bipolar, with injustice being its opposite construct. Based on this assumption, organizational injustice has been equated with low levels of organizational justice, and has been measured accordingly. However, the bipolar assumption has yet to be empirically tested, giving validity to the use of existing scales of justice for the measurement of injustice. The present study removes all assumptions of the relationship between organizational justice and injustice. A model and understanding of injustice is developed based on qualitative analysis of employees’ experiences of both justice and injustice. Semi-structured interviews are conducted to extract experiences of organizational injustice, and the role of emotion in the experience of justice and injustice. The qualitative data is analyzed using the grounded theory approach, and it is concluded that organizational justice and injustice are not bipolar constructs occupying a single continuum of perceptions. Results call for a more accurate measurement tool of injustice.
Covers not scanned.
Keywords: Organizational justice; Polarity (Psychology)